The Pengaruh Ukuran perusahaan dan Ukuran Komite Audit terhadap Pengungkapan Corporate Social Responsibility: Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar Pada BEI Tahun 2014-2018 - Jaenal Abidin; Siska Anggun Lestari (Owner : Riset dan Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of company size on corporate social responsibility disclosure and to determine the effect of audit committee size on corporate social responsibility disclosure, and to determine the effect of company size and audit committee size together on corporate social responsibility disclosure in mining companies in the period 2014-2018. Data collection using secondary data obtained from the Indonesia Stock Exchange. The population in this study are mining companies listed on the Indonesia Stock Exchange. Sampling with puposive sampling method, there are 155 samples. The method of analysis uses multiple linear regression. The results of the study concluded that the size of the company and the size of the audit committee simultaneously had a significant effect on corporate social responsibility disclosure, company size had no significant effect on corporate social responsibility disclosure, and the size of the audit committee had a significant effect on corporate social responsibility disclosure.